INDEKS PENULIS VOLUME 30 - Jurnal Teknologi Industri Pertanian (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Abdullah, R. 167 Adnan, A.A. 180 Agusti, F.A. 151 Ali, M.M. 308 Ardiansyah, R. 234 Arkeman, Y. 100, 362 Darmawan, M.A. 281 Darmawati, E. 1 Darusalam, L.Y. 244 Djatna, T. 82 Dzulkarnain 53 Erni, N. 167